PENGGUNAAN MEDIA PEMBELAJARAN DALAM PENGAJARAN BAHASA INDONESIA - Dwi Viora; Endang Wahyuningsi; Yenni Fitra Surya; Rusdial Marta (JURNAL PENDIDIKAN ROKANIA, 2021)
The purpose of this study is to describe "Use of Learning Media in Teaching Acepte Indonesian". This type of research is conceptual research. Based on the discussion, it can be concluded 5 things, namely (1) learning media are tools, methods, and techniques used to assist the learning process; (2) the benefits of learning media are to simplify and clarify and make learning more interesting; (3) the function of learning media is as a tool for both teachers and students to achieve targeted learning outcomes; (4) the types of learning media are divided into three, namely media in terms of their nature, in terms of their reach, and in terms of their use; (5) The use of media in teaching Indonesian is related to the material and learning objectives to be achieved, also associated with the availability of facilities and infrastructure in schools or those that can be used by teachers to support an effective and targeted learning process.